The Templars, the Hospitallers and the Crusades: essays in homage to Alan J. Forey - Nicholson, Helen J.; Burgtorf, Jochen; Forey, Alan (The military religious orders, 2020)
"This book is homage to the work of a scholar who has substantially advanced scholarship on the medieval military religious orders. Alan J. Forey has published over seventy meticulously researched articles on every aspect of the military religious orders, two books on the Templars in the Corona de Aragón, and a wide-ranging survey of the military religious orders from the twelfth to the early fourteenth centuries. His archival research has been especially significant in opening up the history of the military orders in the Iberian Peninsula. This volume comprises an appreciation of Forey's work and a range of research that has been inspired by his scholarship or develops themes that run through his work. Articles reflect Forey's detailed research into and analysis of primary sources, as well as his work on the military orders, the crusades, the eastern Mediterranean and the trial of the Templars. Further papers move beyond the geographical and chronological bounds of Forey's research, while still exploring his themes of the military religious orders' relations with the Church and State"--